Metformin inhibits spontaneous excitatory postsynaptic currents in spinal dorsal cord neurons from paclitaxel-treated rats - Liu, Ting-Ting; Qiu, Chun-Yu; Hu, Wang-Ping (Frontiers in Synaptic Neuroscience, 2023)
Cancer patients treated with paclitaxel often develop chemotherapy-induced peripheral neuropathy, which has not been effectively treated with drugs. The anti-diabetic drug metformin is effective in the treatment of neuropathic pain. The aim of this study was to elucidate effect of metformin on paclitaxel-induced neuropathic pain and spinal synaptic transmission. The present data demonstrated that intraperitoneal injection of paclitaxel produced mechanical allodynia and potentiated spinal synaptic transmission. Intrathecal injection of metformin significantly reversed the established mechanical allodynia induced by paclitaxel in rats. Either spinal or systemic administration of metformin significantly inhibited the increased frequency of spontaneous excitatory postsynaptic currents (sEPSCs) in spinal dorsal horn neurons from paclitaxel-treated rats. We found that 1 hour incubation of metformin also reduced the frequency rather than the amplitude of sEPSCs in the spinal slices from paclitaxel-treated rats. These results suggested that metformin was able to depress the potentiated spinal synaptic transmission, which may contribute to alleviating the paclitaxel-induced neuropathic pain.